O uso da língua portuguesa para estudantes surdos na licenciatura de letras-libras: uma análise da perspectiva de discentes surdos - Franco, Ednilton Barreto (Brasil, 2023)
My experience in the classroom as a pre-service deaf teacher in the Degree in Literature-Libras at UFAM was the motivation for this research, which has the general objective: To analyze the challenges of deaf students in literacy in written Portuguese as an additional language (LA ) in the Literature-Libras Course at the Federal University of Amazonas. Specific objectives: Reflect on the use of written Portuguese from the perspective of students of the Language and Libras Course at the Federal University of Amazonas. To investigate how it happens in the literacy process of using the written Portuguese language in the Libras-Libras course for deaf students. The theoretical basis was divided into two parts: deaf academics and the linguistic context in the academy with theorists: Wilcox; Wilcox (2005), Soler; Martins (2022), Leffa; Irala (2014), Reis (2015), Simplício; edges; Lima (2019), Oliveira (2014), Bisol et al (2010) and Lebedeff (2004); on literacy in Portuguese as an LA as a strategy for deaf academics, based on Guerretta (2017), Pires (2020) and Simplício; edges; Lima (2019). The methodological procedures are qualitative research (GIL 2008; YIN, 2016; PAIVA, 2019), with context in the UFAM Language and Literature course, with five participants. For data generation, questionnaires were used and for data analysis, content analysis was used based on Bardin (2016). The results show that written Portuguese and literacies are strategies that help in the learning practices of pre-service deaf teachers.